Frequencies and results of anti-nuclear, anti-dsDNA and anti-ENA in a tertiary-care hospital in Karachi, Pakistan - Fatima Husain Kanani; Tahir Hussain; Tayyaba Talat; Nida Ghouri (Journal of the Pakistan Medical Association, 2020)
Objectives: To analyse frequencies and results of anti-nuclear antibodies, anti-double stranded deoxyribonucleic acid and anti-extractable nuclear antigens tests ordered in a tertiary-care hospital. Method: The retrospective study was conducted at a tertiary care hospital in Karachi, and comprised all tests ordered for anti-nuclear antibodies, anti-double stranded deoxyribonucleic acid and anti-extractable nuclear antigens from March 2017 to January 2018. Data was retrieved from the institutional electronic database. The frequencies and results of the tests were determined. Anti-nuclear antibodies test was determined by indirect immunofluorescence, while the other two tests were determined by enzyme-linked immunosorbent assay. Patterns emerging from anti-nuclear antibodies tests were also analysed. Results: Of the 1053 tests ordered, 1000(95%) were for anti-nuclear antibodies.. It was positive in 260(26%) patients, and was repeated in 8(3%) of the positive and 9(1.2%) of the negative patients. Anti-double stranded deoxyribonucleic acid test was ordered in 300(40.5%) and anti-extractable nuclear antigens test in 125(17%) patients who had tested negative for anti-nuclear antibodies. Among those who tested positive for anti-nuclear antibodies, the commonly observed patterns were homogenous 109(41.9%) and speckled 103(39.6%). Rod and ring pattern was seen in 10(3.8%) patients, and none of them was on anti-viral treatment. Conclusion: There was injudicious and unjustified ordering of auto-antibodies testing, indicating the need for greater physician education and cost-effective protocols. Key Words: Auto-antibodies, Homogenous, Speckled, Rod and ring pattern, Hepatitis C, Continuous...